The Use of TikTok Affiliate Marketing for e-Commerce and Online Business - Melinda Christanti Kwan (PT Naureen Digital Education, 2023)
For a commission, affiliate marketers sell the goods and services of other businesses. By selling products online, you (the affiliate) have the chance to make money without having to deal with the difficulties of developing a product or establishing up shop in the traditional sense. Instead, product developers or retailers who have ready-to-use items launch an affiliate program where internet marketers urge their online readers, viewers, or contacts to purchase the products. Because each affiliate marketer has a distinct link, the product developers can identify who directs customers to their site to make purchases, and in exchange, they pay the affiliate marketers a portion of what these customers spend there. The purpose of this study is to learn more about and gain an understanding of how to use affiliate marketing as a fresh approach to promoting a company's worth and revenue. This affiliate marketing plan impact study combines descriptive qualitative research from the library with research done by gathering library data or looking at research items using a variety of library information (books, encyclopedias, scientific journals, or literature studies). The findings demonstrated that the respondents' use of marketing strategy led to an increase in sales over the previous period. This demonstrates how effective affiliate marketing methods can be for online entrepreneurs, especially for those who are growing their companies to the point of success. Sales growth for businesses is greatly aided by an affiliate marketing approach.